Breastfeeding and health care: A multidisciplinary study in a military hospital in Rio de Janeiro, Brazil (Research, Society and Development, 2024)
Social rights, public policies and breastfeeding are of great importance in Brazil. The National Policy for the Promotion, Protection and Support of Breastfeeding is structured around strategic actions that permeate the professional activities of the multidisciplinary team at the Marcílio Dias Naval Hospital (HNMD). The aim of this article is to understand the policy for promoting, protecting and supporting breastfeeding at the Marcílio Dias Naval Hospital, taking into account multidisciplinary work. This is a questionnaire survey with a qualitative approach, using a descriptive, exploratory study in the field of breastfeeding promotion, protection and support to identify phenomena that reflect the concept of multiprofessional health care. Content analysis was carried out according to Bardin's proposal. It was found that the multidisciplinary team, despite having knowledge in the field of breastfeeding, sees the need for continued training and prioritization of actions in this field, with a view to maintaining the quality of the services provided in the mother and child area. It was concluded that there are challenges on a daily basis, with some opportunities for improvement. However, specific situations with users are attended to with zeal and care, with the aim of promoting rights; despite the gaps to be filled and the challenges to be overcome, there is applicability of the policy to promote, protect and support breastfeeding at the HNMD, with a multidisciplinary team committed to materializing this policy, with a permanent focus on optimizing processes and maximizing the level of service in patient care, with the aim of offering excellent services.